Recent advances in EST sequencing in Crassostrea gigas: towards the sequencing of the Pacific oyster genome - Boudry, P.; Huvet, Arnaud; Lapegue, S.; Sauvage, C.; Tanguy, A.; Moraga, D.; Goostrey, A.; Prunet, Patrick; Boulo, V.; Guéguen, Y.; Moal, J.; Fleury, Elodie; et al. (CCSD, 2007)
National audience